Penerapan Hukuman Mati Tindak Pidana Korupsi di Indonesia Ditinjau dari Sisi Hak Asasi Manusia - Effendy, Andry; Magno, Nuno Gilherino Pacheco (Sekolah Tinggi Ilmu Hukum Prof Gayus Lumbuun, 2024)
The rampant corruption that has plagued Indonesia recently has prompted law enforcement officials to continuously strive and brainstorm hard on how to impose punishments or sanctions that can deter corrupt individuals and those contemplating such despicable acts. Many suggestions and viewpoints have been put forth by observers and legal experts in the country regarding appropriate punishments for corrupt individuals to instill a sense of deterrence among wrongdoers and provide a